Impact of Banking Real Estate as an Asset Class on Financial System Stability: Monitoring, Forecasting, Management - Sternik, S.G.; Teleshev, G.V. (Journal of Reviews on Global Economics, 2018)
In this article, we discuss interdependency between real estate markets and financial stability. To study this relationship, we analyze Russian banking sector real estate assets structure and observe material concentration of real estate assets on largest banks' books as well as anticipate that this may present a unique challenge for Russian banking regulator. We propose the development of system of indicators for strategic portfolio management for banking real estate and outline broad directions for further research on the subject to meet this challenge and mitigate potential risks for the banking sector.